Effects of inorganic surface blocking layer of SnS on the performance and stability of perovskite solar cells. (15th November 2020) - Kumar, Y.; Pérez, Teresa Díaz; Jaramillo-Quintero, Oscar Andrés; Regalado-Pérez, E.; Moreno Romero, Paola M.; Mathews, N.R.; Pérez-Tijerina, E.; Mathew, X.
Abstract: Incorporation of SnS as a blocking layer at the interface of TiO2 and CH3 NH3 PbI3 (MAPbI3 ) perovskite has been investigated. With respect to the control, the inclusion of a 3 nm SnS layer via thermal evaporation leads to an improved power conversion efficiency as well as stability, under similar storage conditions. The highest power conversion efficiency of approx. 13.6% is achieved for the champion cell (average ̴ 12%) and stability study over the period of 4 weeks revealed the retention of approximately 85% of its initial efficiency (average 83%). The surface photovoltage spectroscopy (SPV) measurements confirmed that the improvement in the photovoltaic performance is due to the lower photogenerated electron lifetime exhibited by devices with the SnS blocking layer which in turn is attributed to the reduction of trap states at the TiO2 -perovskite interface, decreasing the interfacial charge recombination. Electrical impedance spectroscopy (EIS) and photoluminescence (PL) spectroscopy, additionally endorse the reduction of traps and recombination centers. Highlights: Incorporation of SnS as blocking layer at TiO2 - CH3 NH3 PbI3 perovskite interface. Improved stability with respect to the initial efficiency (retention of ~ 85%). Average power conversion efficiency rises by 25% (best cell increases by 36%). Enhanced electronic coupling and interface passivation. Surface photovoltage (SPV) measurements confirm reduction in trap states.